2022
DOI: 10.1021/acsanm.2c02892
|View full text |Cite
|
Sign up to set email alerts
|

ZnO–Plasma Polymer Fluorocarbon Thin Films for Stable Battery Anodes and High-Output Triboelectric Nanogenerators

Abstract: In this study, ZnO−plasma polymer fluorocarbon (PPFC) nanocomposite thin films were prepared by a mid-range frequency sputtering method using ZnO−polyfluoroethylene−carbon nanotube hybrid targets, and their optical, physical, and surface properties were investigated as functions of the ZnO concentration in the targets. The obtained films exhibited excellent visible light transmittance and hydrophobic characteristics, while their surface roughness and refractive index increased with increasing the ZnO concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Ring-shaped light scattering patterns were observed depending on the orientation of the scatterers, suggesting that individual SiO x species are well scattered at regular spacing without formation of agglomerates in the thin-film. [33][34][35] In-plane scattering profiles were also observed from the inset image at the Yoneda wing position. The scattering angles are reported as the scattering vector q, which incorporates the wavelength of the Xray source 𝜆.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ring-shaped light scattering patterns were observed depending on the orientation of the scatterers, suggesting that individual SiO x species are well scattered at regular spacing without formation of agglomerates in the thin-film. [33][34][35] In-plane scattering profiles were also observed from the inset image at the Yoneda wing position. The scattering angles are reported as the scattering vector q, which incorporates the wavelength of the Xray source 𝜆.…”
Section: Resultsmentioning
confidence: 99%
“…The TF-SiO x 60/PPFC developed in this study is one of the best of all papers reported for using Si-based anodes in terms of cycle life and capacity retention. The fabrication method using these mixed targets had the advantage of depositing various materials (Cu, [33] Ag, [34] and ZnO [35] ), suggesting that high-quality thinfilms for TF-LIBs can be deposited using materials other than SiO x . Figure 5d schematically shows the operating mechanism for the proposed TF-SiO x 60/PPFC TF-SiO x 100 thin-films based on the above results and discussions.…”
Section: Resultsmentioning
confidence: 99%
“…The lithium storage capacity of all thin films was assessed using galvanostatic charge-discharge profiles within a voltage range of 0-2 V Li versus Li/Li + at a current rate of 0.05C (the theoretical capacity at 1C is 987 mAh g À1 , and the theoretical mass density is 5.61 g cm À3 ). [35] Figure 4a-d presents the initial five charge-discharge curves for both the ZnO and ZnO/PTFE thin films. Notably, at the slow current rate of 0.05C, the ZnO and ZnO/PTFE (5,10,15) thin films demonstrated high initial discharge capacities of 2741, 2654, 2577, and 1946 mAh g À1 , corresponding to volumetric capacities of 15 079, 14 867, 14 434, and 10 786 mAh cm À3 and areal capacities of 0.18, 0.178, 0.173, and 0.129 mAh cm À2 , respectively.…”
Section: Electrochemical Evaluation Of Zno and Zno/ptfe Thin-film Anodesmentioning
confidence: 99%
“…This aspect is diversified to further enhance performance. Consequently, ZnO metal oxide performs with a high specific capacity of approximately 978 mAh•g −1 , exceptionally well as a supercapacitor electrode material [17][18][19]. In this context, Zhang et al conducted the synthesis of ZnO with nano-rod geometry on a silicon wafer and found a specific capacitance (Cs) of 43 mF•cm −2 at a current density of 1 mA•cm −2 [20].…”
Section: Introductionmentioning
confidence: 99%